Enthalpy increments and redox thermodynamics of SrFeO3−δ. Issue 19 (14th October 2019) - Sereda, Vladimir; Sednev, Anton; Tsvetkov, Dmitry; Zuev, Andrey
Abstract: Abstract : Enthalpy increments, Δ _298^TH^0, for highly nonstoichiometric SrFeO3−δ (δ = 0.18–0.41) were obtained between 373 and 1273 K in air using drop calorimetry. The analysis of the Δ _298^TH^0( T ) dependence at lower temperatures allowed evaluating the enthalpy of tetragonal to cubic I4 / mmm f="TeX CM Bold Maths Symbols"33 Pm3m phase transition at 560 K, 1.57 kJ/mol, and the Maier–Kelley function for Δ _298^TH^0( T ) of tetragonal SrFeO3−δ (space group I4 / mmm ). Combined investigation of oxygen nonstoichiometry ( T ) dependence, measured by thermogravimetry, and higher-temperature Δ _298^TH^0( T ) of cubic SrFeO3−δ (space group Pm3m ) yielded the temperature-dependent reduction (oxygen release) enthalpy, Δ H_red^0 . Calorimetrically-determined Δ H_red^0 of SrFeO3−δ increases from 65 ± 7 kJ/mol O at 873–973 K to 84 ± 7 kJ/mol O at 1073–1273 K, which may indicate that the short-range vacancy ordering in SrFeO3−δ is hampered at higher temperatures.